2003
DOI: 10.1155/2003/104879
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Amplification by Serum Carrier Protein Binding

Abstract: Mass spectroscopic analysis of the low molecular mass (LMM) range of the serum/plasma proteome is a rapidly emerging frontier for biomarker discovery. This study examined the proportion of LMM biomarkers, which are bound to circulating carrier proteins. Mass spectroscopic analysis of human serum following molecular mass fractionation, demonstrated that the majority of LMM biomarkers exist bound to carrier proteins. Moreover, the pattern of LMM biomarkers bound specifically to albumin is distinct from those bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
0
2

Year Published

2004
2004
2007
2007

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(135 citation statements)
references
References 35 publications
2
131
0
2
Order By: Relevance
“…The retention of albumin in unfractionated serum samples may be essential to the diagnostic power of information gleaned from serum through this method. We recently demonstrated that albumin and other carrier proteins of high abundance avidly bind low molecular weight proteins and peptide fragments (33). Such low molecular weight molecules are the underpinning of the diagnostic patterns identified by this approach.…”
Section: Discussionmentioning
confidence: 99%
“…The retention of albumin in unfractionated serum samples may be essential to the diagnostic power of information gleaned from serum through this method. We recently demonstrated that albumin and other carrier proteins of high abundance avidly bind low molecular weight proteins and peptide fragments (33). Such low molecular weight molecules are the underpinning of the diagnostic patterns identified by this approach.…”
Section: Discussionmentioning
confidence: 99%
“…that overwhelm the less abundant signals. Methods to remove these abundant proteins have been developed; however, recent studies have found that many peptide fragments (potential biomarkers) circulate bound to albumin (24). Albumin acts as a sink or reservoir for these molecules and greatly prolongs their half-life from minutes to days (25).…”
Section: Step 3: Desired Site Of Clinical Measurementmentioning
confidence: 99%
“…These compounds may also reflect the physiologic state of the tumor and reveal the effects that the tumor has on the organism itself (2 ). Tumor-derived proteins that are produced in very low concentrations enter the circulation and bind to transport proteins (3,4 ). Sequestration of these peptides by carrier proteins that are present in high concentrations and have long half-lives, such as albumin, protects these markers from clearance and helps amplify their concentration in the circulation.…”
mentioning
confidence: 99%